Liraglutide Attenuates Hepatic Ischemia–Reperfusion Injury by Modulating Macrophage Polarization - Li, Shang-Lin; Wang, Zhi-Min; Xu, Cong; Che, Fu-Heng; Hu, Xiao-Fan; Cao, Rui; Xie, Ya-Nan; Qiu, Yang; Shi, Hui-Bo; Liu, Bin; Dai, Chen; Yang, Jun (Frontiers in Immunology, 2022)
Ischemia-reperfusion injury (IRI) is a common complication in liver surgery. Previous studies demonstrate that macrophages play an important role in the process of hepatic IRI. Liraglutide is a glp-1 analog (glucagon-like peptide-1) that is primarily used in the treatment of type 2 diabetes and obesity, which also be used to regulate intracellular calcium homeostasis to protect cardiomyocyte injury. However, its role in hepatic IRI has not been fully understood. This study aimed to investigate whether liraglutide could protect the liver from IRI and determined the possible mechanisms. Our results showed that liraglutide pretreatment significantly alleviate liver damage cause by IRI, as evidenced by HE staining, serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) and TUNEL staining which can evaluate the degree of live injury. Meanwhile, the inflammatory cytokines elicited by IRI were distinctly suppressed after liraglutide pretreatment, accompanied by significant reduction in TNF-α, IL-1β and IL-6. Furthermore, pretreatment with liraglutide markedly inhibited M1 polarization during hepatic IRI, as revealed by a significant decrease in CD68+ of Kupffer cells detected by flow cytometry. However, the protective effects of liraglutide on hepatic IRI were partly diminished in GLP-1R knockout mice. In vitro study, we assessed the role of liraglutide in macrophage polarization by examining the expression profiles of M1 in BMDMs from GLP-1R-KO mice and C57BL/6J mice. In keeping with vivo study, liraglutide attenuated LPS-induced M1 polarization and showed an expression pattern of decreased M1 markers. However, the inhibitory effect of liraglutide on LPS-induced M1 polarization was largely abolished in BMDMs from GLP-1R-KO mice. Taken together, our study indicated that liraglutide can ameliorate hepatic IRI through regulating macrophages polarization by GLP-1R on macrophage. The protective effect of liraglutide on liver IRI suggests that liraglutide may be an appropriate drug for clinical treatment of liver IRI.